2017
DOI: 10.1039/c6md00569a
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationships for the synthesis of selective cyclooxygenase 2 inhibitors: an overview (2009–2016)

Abstract: Most drugs used to treat pain and inflammation act through inhibition of the enzymes prostaglandin G/H synthase, commonly known as cyclooxygenase (COX). Among these, the simultaneous inhibition of cyclooxygenase 1 (COX-1) would explain the unwanted side effects in the gastrointestinal tract and many adverse cardiovascular effects, such as high blood pressure, myocardial infarction and thrombosis. These side effects led in time to the development of NSAIDs that behave as selective COX-2 inhibitors. This manuscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 61 publications
1
40
0
1
Order By: Relevance
“…A preliminary docking study was performed to provide an insight into the interaction of the naproxen-dehydrodipeptide scaffold with the active site of the COX-1 and COX-2 isoenzymes [29,30] (Figure 7, Table 2). The crystal structures of COX-1 and COX-2 enzymes show a high degree of sequence homology (~60%), but, nevertheless, there are key differences between the active sites [39,40]. The Ile-434 and Ile-523 residues of COX-1 are switched for smaller valine residues in COX-2 [39].…”
Section: Effect Of the Compounds On Cox-1/cox-2 Activitymentioning
confidence: 99%
“…A preliminary docking study was performed to provide an insight into the interaction of the naproxen-dehydrodipeptide scaffold with the active site of the COX-1 and COX-2 isoenzymes [29,30] (Figure 7, Table 2). The crystal structures of COX-1 and COX-2 enzymes show a high degree of sequence homology (~60%), but, nevertheless, there are key differences between the active sites [39,40]. The Ile-434 and Ile-523 residues of COX-1 are switched for smaller valine residues in COX-2 [39].…”
Section: Effect Of the Compounds On Cox-1/cox-2 Activitymentioning
confidence: 99%
“…К настоящему времени накоплено достаточно данных о вовлеченности его в процесс канцерогенеза [23]. Показано защитное действие ингибиторов COX-2 в колитассоциированном опухолегенезе и при ряде других локализаций [24].…”
Section: экспериментальные статьиunclassified
“…Studying the structures of most selective COX-2 inhibitors revealed the presence of diaryl substitution on carbocyclic or heterocyclic core ( Figure 1). Moreover, structure-activity relationship (SAR) studies of COXIBs showed that a COX-2 selectivity raised due to a hydrophobic interaction with an extra hydrophobic region and polar interactions with a secondary polar pocket that are found in COX-2 isozyme [18]. Moreover, the presence of electron withdrawing group in one of the aryl substitutions in the para position is more preferable than corresponding electron donating group [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, structure-activity relationship (SAR) studies of COXIBs showed that a COX-2 selectivity raised due to a hydrophobic interaction with an extra hydrophobic region and polar interactions with a secondary polar pocket that are found in COX-2 isozyme [18]. Moreover, the presence of electron withdrawing group in one of the aryl substitutions in the para position is more preferable than corresponding electron donating group [18]. Various previous studies were implemented to synthesize selective COX-2 inhibitors by using different methods [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation